Mechanisms Of Supportive Institutions In The Development Of The Islamic Financial Industry - Younes Chouaib; Barani Abdennasser; Bellamouchi Ali (جامعة الوادي University Of Eloued, 2024)
The Islamic finance sector is considered an essential tool for mobilizing resources in the present time by providing necessary cash liquidity for investment and development, thus generating profits and revenues for its owners. In order to integrate this financial tool into the economy, it is necessary to provide the appropriate environment for its success and development.This involves leveraging supportive organizations to foster the growth of Islamic finance. The study concluded that it is possible to benefit from these institutions to develop the Islamic financial industry, through coordination between them to provide an integrated environment to ensure its effectiveness, as well as the development of laws and supervisory and regulatory bodies for this industry, which will qualify it to play its role as a tool for growth in the service of the economy.
Keywords: supporting institutions; Islamic financial industry; Islamicfinance products; Islamic bank